220 Preventing ACL reinjuries – is persistent knee underloading at return to sports after reconstruction the culprit?. (3rd March 2020) - Kotsifaki, Argyro; Sideris, Vasileios; Korakakis, Vasileios; Whiteley, Rod
Abstract : Background: Hop tests are part of the discharge criteria to determine return to sports (RTS) following anterior cruciate ligament reconstruction (ACLR). Usually, only the distance hopped is measured, but little is known regarding biomechanical performance during these tests. Objective: Describe biomechanical parameters of ACLR patients during single and triple hop for distance at the time of RTS. Design: Cross-sectional study. Setting: Laboratory, level I sport athletes. Patients (or Participants): 28 males: 14 primary ACLR patients (24±6 years) who were cleared to RTS, 14 healthy recreational athletes (30±5). Interventions (or assessment of risk factors): Biomechanical differences between limbs and groups. Main outcome measurements: Knee power absorption and generation during the propulsion and landing phases of single and triple hops. Results: Despite similar hop distance, ACLR patients had significantly lower between-limb knee power generation (d=1.12, p=0.001), and absorption (d=1.00, p=0.002) during single hop and less power compared to controls in both phases (d=0.78, p=0.05). During triple hop, ACLR patients displayed less knee power generation in the first (d=1.11, p=0.001) and second hop (d=1.14, p=0.001) and less power absorption in the final landing (d=0.73, p=0.017) in comparison to the uninvolved leg. Similarly, ACLR patients had less knee power generation in the first (d=1.69, p=0.000) and second hop (d=1.21, p=0.004) and less absorption in the final landing (d=1.09, p=0.008) compared to the control group. Conclusions: ACLR patients underload their injured knee despite meeting hop distance targets to be cleared to RTS. This pattern has not been documented previously and could explain the high risk of reinjury to the knee and other structures in the kinetic chain after RTS.